Asociación de la percepción de estrés de los estudiantes que cursan asignaturas preclinicas con los que cursan asignaturas clínicas en la Escuela de Odontología de la UPC durante el 2013 - Terán Chávez, Edith Stephanie (2014)
Objective: Determine the association of perceptions of stress in preclinical and clinical students who attend to the School of Dental Medicine at UPC in 2013. Material and methods: A survey was conducted to 222 students of the School of Dental Medicine at UPC. To measure stress levels, we used the Dental Environment Stress questionnaire created by Garbee (1980) and amended and validated in Spanish by Fonseca (2012). Data such as age, sex and year of study was collected in a file made for this study. Results: We found that clinical students have 2.96 more risk of having stress than preclinical students. Within these categories, in preclinical level, first years students show the higher stress levels (68.2% in moderately stressful and very stressful 15.1%), while in clinical levels, third year students had the higher stress level (80.9% in moderately stressful and 19% in very stressful). Our data show no association between sex and stress level of the students (p=0.508). Conclusions: Clinical students show more stress level with 2.96 times higher risk for stress compared to preclinical students. In preclinical level, first years students showed the higher stress level, while in clinical level, third years students had the higher stress level. Our data show no association between sex and stress level of students.